Numerical methods in mechanics of materials : with applications from nano to macro scales /: with applications from nano to macro scales. (2017) - Chong, K. P (Ken Pin), 1942-; Boresi, Arthur P (Arthur Peter), 1924-; Saigal, Sunil; Lee, James D
No abstract available